Potret Gaya Hidup Remaja Urban dalam Novel 12 Cerita Glen Anggara Karya Luluk Hf - Noviani, Isra Rahma; Zulfadhli (Universitas Negeri Padang, 2024)
Portrait of the lifestyle of urban teenagers which is a form of life in explaining phenomena that occur in urban society. Urban society itself has different characteristics from rural society which can be seen from the way of thinking and the surrounding environment. One of the novels that can be seen is a portrait of urban teenagers entitled 12 Stories of Glen Anggara by Luluk HF. The life of urban teenagers is explained through the characters' behavior with their environment, such as towards friends and family, which influences their lifestyle. This research is included in qualitative research which uses descriptive methods. This research aims to describe: (1) a portrait of the lifestyle of urban teenagers regarding the prestige of recreation in the novel 12 Stories Glen Anggara by Luluk HF, (2) a portrait of urban teenagers about the instant lifestyle in the novel 12 Stories Glen Anggara by Luluk HF, (3) portrait of an urban teenager about an individualistic lifestyle in the novel 12 Stories Glen Anggara by Luluk HF, (4) portrait of an urban teenager about a virtual lifestyle in the novel 12 Stories Glen Anggara by Luluk HF. The data collection technique for this research involves reading and understanding from the beginning to the end of the novel first, then marking the parts that are research points in terms of lifestyle portraits, determining the main characters in the novel and inventorying the data in a format. The data validation technique used is the triangulation technique. The triangulation technique is carried out by creating various versions of questions, examining various data sources, utilizing various methods. The research findings on portraits of urban teenagers' lifestyles in the novel 12 Stories of Glen Anggara by Luluk HF include portraits of recreational prestige, portraits of instant lifestyles, portraits of individualist lifestyles, and portraits of virtual lifestyles